sin 2 1 ∘ + sin 2 2 ∘ + sin 2 3 ∘ + … + sin 2 8 8 ∘ + sin 2 8 9 ∘ + sin 2 9 0 ∘ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
cos x = sin ( 9 0 ∘ − x ) The equation thus becomes sin 2 1 ∘ + cos 2 1 ∘ + sin 2 2 ∘ + cos 2 2 ∘ + … + sin 2 4 4 ∘ + cos 2 4 4 ∘ + sin 2 4 5 ∘ + sin 2 9 0 ∘ .
We know that sin 2 x + cos 2 x = 1 for all real x , thus we have the given expression as 1 + 1 + 1 + 1 + 1 + . . . + 1 + sin 2 4 5 ∘ + sin 2 9 0 ∘ = 4 4 + 0 . 5 + 1 = 4 5 . 5 . □
Problem Loading...
Note Loading...
Set Loading...
We'll be using the Pythagorean identity that states sin 2 ( x ) + cos 2 ( x ) = 1 and the cofunction identity that says cos ( 9 0 − x ) = sin x
Using these identities, we see that cos 2 ( 1 ) = sin 2 ( 8 9 ) , cos 2 ( 2 ) = sin 2 ( 8 8 ) , cos 2 ( 3 ) = sin 2 ( 8 7 ) . . .
Therefore, ignoring the sin ( 9 0 ) , we find that there are 44 pairs of Pythagorean identities that each sum to 1.
Now we are just left with sin 2 ( 4 5 ) and sin ( 9 0 ) 2 .
Well this is easy! sin 2 ( 4 5 ) = ( 2 1 ) 2 = 2 1 and sin ( 9 0 ) 2 = 1 1 2 = 1
Therefore, we have 4 4 + 1 + 0 . 5 = 4 5 . 5